Pengaruh Motivasi Kerja, Disiplin Kerja, Lingkungan Kerja terhadap Kinerja Karyawan PT. X - Farah Nadiyah Apriliany; Wawa Santoso (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The research's purpose of this study was to examine the influence of the independent variables of work motivation, work discipline and work environment on the dependent variable, employee performance at PT. Century Mitra Sukses Sejati. The object in this research is PT. Century Mitra Sukses Sejati located in the Cikupa industrial area, Tangerang. The sampling technique is by saturation sampling with a total of 126 employees. Data acquisition was carried out by distributing questionnaires. The data analysis method used in this study was multiple linear regression analysis .